Pengelolaan Program Pengabdian bagi Alumni di Pondok Modern Assalam Putri Sukabumi - Elsa Sahara; Nan Rahminawati; Eko Surbiantoro (UNISBA Press, 2024)
Abstract. The output of this service program is to make alumni as prospective educators who have four teacher competencies, namely pedagogic, personality, social, and professional. along with one of the problems of Indonesian education, the quality of teachers. The service program was formed since the beginning of the establishment of Pondok Modern Assalam, there has been no change in all aspects, therefore, the author is interested in how the management of the service program can last a long time, so the author raised the title of the research